Three‐dimensional printing for surgical planning in complex congenital heart disease. Issue 11 (26th August 2019) - Vettukattil, Joseph J.; Mohammad Nijres, Bassel; Gosnell, Jordan M.; Samuel, Bennett P.; Haw, Marcus P.
Abstract: Surgical management of complex congenital heart disease (CHD) is challenging. Three‐dimensional (3D) printing can improve multidisciplinary team decision‐making, patient and family understanding, and education of medical professionals. We describe 3D printing for surgical management of five patients with complex CHD. The anatomical details of the 3D printed models were instrumental in planning surgical techniques especially in determining between single ventricle, 1.5 ventricle, and biventricular repair.